Mental toughness in Icelandic female football players : comparisons of the national team, top and second top women's divisions - Dagrún Birta Karlsdóttir 1999- (2023)
Football is a competitive team sport requiring top performance and technical, tactical, physical, and psychological skills. Mental toughness is an umbrella term used to define the mental traits of athletes who perform well in practice and competition while others struggle. Mixed method research was used. The study's goal was to compare the quantitative study of potential differences in mental toughness among Icelandic women's football players with a qualitative study of the players' views on the term. The quantity study consisted of 142 female football players (32 from the national team, 56 from the first division and 54 from the second division) aged between 17 and 33. A self-report questionnaire including the Sport Mental Toughness Questionnaire (SMTQ) was used to assess three aspects of mental toughness (confidence, constancy, and control). Players exhibit a higher level of mental toughness at a higher level of competition. National team players reported the highest levels of mental toughness, players in the first division had the second highest level of mental toughness and lastly players in the second division. The qualitative study consisted of 6 female football players (2 players from each division; national team, first and second division). Most interviewees claimed that a player needs more mental toughness as the competitive environment becomes more challenging. Furthermore, there would need to be a change in football training in Iceland, focusing more on the mental aspects of training. Keywords: mental toughness, women's football, type of division, mixed method research Fótbolti er liðsíþrótt sem krefst tæknilegrar, taktískrar, líkamlegrar og andlegrar færni til að ná sem bestum árangri. Andleg harka er regnhlífarhugtak sem notað er til að skilgreina andlega eiginleika íþróttamanna sem standa sig vel á æfingum og keppni. Notast var við blandað rannsóknarsnið. Markmið rannsóknarinnar var að bera saman megindlega rannsókn á mögulegum mun á andlegri hörku íslenskra knattspyrnukvenna við eigindlega ...